Die Wandelnde Mandel - Manfred Winkler und Paul Celan - Sekiguchi, Hiroaki (Naharaim, 2025)
Manfred Winkler met Paul Celan, his fellow countryman from Bukovina, in October 1969. At the reading in Jerusalem, Winkler asked Celan whether a line in his poem "da sah ich dich, Mandelstamm" referred to the trunk of the almond tree or the poet Mandelstam. Through this conversation, the images "almond tree" and "almond" became an important cipher for the relationship between Winkler and Celan. After this encounter, Winkler wrote at least 20 poems under the direct influence of Celan, in which he quotes from Celan's vocabulary. In another untitled poem of his, "Mandel" does not appear, but only the word "Niemand". They have the element "mand" in common, probably in allusion to the poet Ossip Mandelstam, who, like Winkler und Celan, symbolizes the poet in exile. Here, the poetic transformation of the almond is driven to the phonetic level of the word. Thus, the almond continues to transform itself in Winkler’s poems, and there is no end to it.